Long-Term Effects of Sinus Floor Elevation with and Without Bone Graft: A Systematic Analysis of Randomized Clinical Trials - Andrei Paul Tent; Ioan Andrei Țig; Simion Bran; Andra Zlotu; Alexandru Mester; Florin Onisor (Medicina)
Background and Objective: The aim of this systematic review was to assess clinical trials on the efficiency of sinus lift techniques with and without bone grafting in the atrophic posterior maxilla. Materials and Methods: This article was written under the PRISMA and the Cochrane Handbook for Systematic Reviews of Interventions guidelines. PubMed, Scopus, and Web of Science databases were electronically searched until December 2023. The risk of bias was assessed according to Cochrane Risk of Bias tool guidelines. Statistical analysis was performed for implant survival rate (ISR), marginal bone loss (MBL), and endo-sinus bone gain (ESBG). Results: At the end of the electronic search, 5 clinical trials were considered eligible. Statistical analysis was achieved for osteotome sinus floor elevation. The ISR at 3 years had a risk ratio (RR) of 0.98 [0.90, 1.07] (CI 95%), p = 0.7, and at 5 years, RR 1.02 [0.93, 1.11] (CI 95%), p = 0.68. The MBL, at 3 years, indicated a weighted mean difference (WMD) of 0.01 [−0.15, 0.16] (CI 95%), p = 0.93, and at 5 years, WMD of −0.08 [−0.53, 0.37] (CI 95%), p = 0.73. ESBG at 3 years had a WMD of −0.44 [−1.05, 0.17] (CI 95%), p = 0.16, and at 5 years, WMD of −0.61 [−1.63, 0.41] (CI 95%), p = 0.24. Conclusions: The available evidence underlines that the osteotome sinus floor elevation technique without bone graft may be used.